(untitled) (Journal of Humanities and Social Sciences Research, 2023)
This research sheds light on the primacy of the hoopoe bird in transmitting the event and its use of the method of suspense at the beginning of the story when he said to The prophet Suleiman: ( I have grasped (the knowledge of a thing) which you have not grasped and I have come to you from Saba’ (Sheba) with true news, It is one of the successful journalist characteristics when you be a witness for any act and transmitted events what your eyes saw. This research came to confirm that the Qur’an emphasized the importance of impartially and honestly reporting the news and conveying the reality without distortion., the hoopoe didn’t transmit the news until he investigated and examined and researched and knew that the village was called Sheba, and it is in the country of Yemen. The phrase: “I have come to you” indicates that knowledge and data were brought from a place outside the place where The prophet Suleiman was. After the research, it was found that these verses in which the story of the hoopoe was mentioned with The prophet Suleiman, were a behavioral rule that guides the behavior of the creature to transmit events honestly.